Cremona Maps of de Jonquières Type. (1st August 2015) - Pan, Ivan; Simis, Aron
Abstract: This paper is concerned with suitable generalizations of a plane de Jonquières map to higher dimensional space P^n with n 3 . For each given point of P^n there is a subgroup of the entire Cremona group of dimension n consisting of such maps. We study both geometric and group-theoretical properties of this notion. In the case where n = 3 we describe an explicit set of generators of the group and give a homological characterization of a basic subgroup thereof.